2022
DOI: 10.3390/jcm11102884
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Findings Associated to Belantamab-Mafodotin (Belamaf) Use in a Series of Patients Examined Longitudinally by Means of Advanced Corneal Imaging

Abstract: Belantamab mafodotin (belamaf) is a novel antibody–drug conjugate developed for the treatment of patients with relapsed or refractory multiple myeloma (RRMM). Although the drug has demonstrated a good efficacy, corneal adverse events have been reported. In this prospective study, consecutive patients with RRMM who received belamaf infusions were included. The standard ophthalmological visit was implemented with anterior segment (AS)-optical coherence tomography (OCT) and in vivo confocal microscopy (IVCM). Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, AS-OCT and IVCM can also provide valuable support for follow-up. [ 17 , 18 ] These changes typically start in the peripheral cornea and then migrate toward the center, affecting vision quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…However, AS-OCT and IVCM can also provide valuable support for follow-up. [ 17 , 18 ] These changes typically start in the peripheral cornea and then migrate toward the center, affecting vision quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Matsumiya et al, increased corneal epithelial thickness following belamaf treatment was demonstrated using AS-OCT measurements. Another study by Mencuci et al demonstrated a transient increase in epithelial thickness in RRMM patients on belamaf followed by a subsequent diffuse decline [ 204 , 212 ].…”
Section: Systemic Conditionsmentioning
confidence: 99%
“…Some studies with diferent designs have evaluated ETM changes after cataract surgery [133,[201][202][203], almost all reporting an increase in the central and midperipheral CET with a gradual decrease to baseline levels within a month [133,[201][202][203]. However, their reported back-to-baseline time points varied; some studies report a return to preoperative levels within 3-7 days [202,203], while some others report longer durations ranging from 5-15 days [201,204] to 4 weeks [133]. In addition, CET reduction to baseline levels can take longer in people with diabetes [202].…”
Section: Cataract Surgerymentioning
confidence: 99%
“…The FDA also authorized belantamab mafodotin, a combination of microtubule inhibitors and antibodies directed against B-cell maturation antigens for the treatment of refractory multiple myeloma. Patients using this medication were shown to potentially develop corneal epithelial alterations resembling microcysts, which needed dose adjustments, reduction, or stop [132][133][134]. Before starting belantamab mafodotin and before each subsequent dose, the FDA advises to have a complete ophthalmological examination [135].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%